2020
DOI: 10.1002/alr.22720
|View full text |Cite
|
Sign up to set email alerts
|

Inferior meatus augmentation procedure (IMAP) normalizes nasal airflow patterns in empty nose syndrome patients via computational fluid dynamics (CFD) modeling

Abstract: Background Empty nose syndrome ENS is a controversial upper airway disorder most commonly associated with tissue loss from the inferior turbinates The inferior meatus augmentation procedure IMAP has been shown to effectively reduce ENS symptoms in a durable manner but the precise mechanisms that may govern this symptomatic improvement remain unknown Methods Five patients with ENS who underwent bilateral IMAP via submucosal costal cartilage implant were assessed Pre-implant and months post-implant computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…2 Blinded computational fluid dynamics assessment of patients with ENS following IMAP demonstrated that this procedure restores normal airflow patterns toward the inferior meatus while concomitantly reducing aberrant airflow through the middle meatus. 3 Importantly, our group has also shown that ENS patients often experience improvements in aspects of their psychological well-being and overall quality of life following IMAP, as determined by significant reductions in the Generalized Anxiety Disorder 7-item scale (GAD-7), and Patient Health Questionnaire-9 (PHQ-9), and Sinonasal Outcome Test (SNOT-22) scores. 2 All score improvements remained statistically significant at 1 year postoperatively, suggesting that the benefits of nasal airway augmentation surgery can be sustained long term.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…2 Blinded computational fluid dynamics assessment of patients with ENS following IMAP demonstrated that this procedure restores normal airflow patterns toward the inferior meatus while concomitantly reducing aberrant airflow through the middle meatus. 3 Importantly, our group has also shown that ENS patients often experience improvements in aspects of their psychological well-being and overall quality of life following IMAP, as determined by significant reductions in the Generalized Anxiety Disorder 7-item scale (GAD-7), and Patient Health Questionnaire-9 (PHQ-9), and Sinonasal Outcome Test (SNOT-22) scores. 2 All score improvements remained statistically significant at 1 year postoperatively, suggesting that the benefits of nasal airway augmentation surgery can be sustained long term.…”
Section: Discussionmentioning
confidence: 92%
“…Patient‐reported nasal breathing outcomes as measured by the ENS6Q showed significant and sustained improvements 1 year following IMAP with cadaveric rib 2 . Blinded computational fluid dynamics assessment of patients with ENS following IMAP demonstrated that this procedure restores normal airflow patterns toward the inferior meatus while concomitantly reducing aberrant airflow through the middle meatus 3 . Importantly, our group has also shown that ENS patients often experience improvements in aspects of their psychological well‐being and overall quality of life following IMAP, as determined by significant reductions in the Generalized Anxiety Disorder 7‐item scale (GAD‐7), and Patient Health Questionnaire‐9 (PHQ‐9), and Sinonasal Outcome Test (SNOT‐22) scores 2 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, we believe patients undergoing IMAP show significant improvements because of the ability of IMAP to restore inferior turbinate volume and thereby normalize aberrant nasal aerodynamics in ENS patients, an effect which has been demonstrated by our collaborative group using computational fluid dynamics analysis in these postoperative patients. 19 Our group has previously reported that IMAP utilizing acellular dermal matrix or SIS graft provides significant improvements in ENS, sinonasal, anxiety, and depression symptoms. 9,10 However, we also reported the limitations of this prior study, which included a small sample size, concurrent sinus surgeries, limited followup, and the transition to a different implant material due to resorption.…”
Section: Discussionmentioning
confidence: 96%